Nutritional supplementation of tomato with the marine algae (Ascophyllum nodosum) - Blanch-Bermúdez, Daniela (2026)
By 2025, global tomato production exceeded 186 million tons. Over the past 30 years, tomato yields have doubled, leading to intensive use of fertilizers. The use of organic fertilizers and other nutrient sources is becoming important for food production. Macroalgae such as Ascophyllum nodosum are of interest as fertilizers since they promote growth, resistance to abiotic stress, and soil quality. A trial was established with the aim of assessing the efficiency of algae as a fertilizer. To do this, the use of soluble chemical fertilizers was compared against a fertilization plan that included algae in addition to a chemical fertilizer supplement. The calculations were made so that both formulations had the same nutritional contribution. The trial was established under a protected environment using coconut fiber as a substrate and with drip fertigation. 90 plants were planted for each treatment. Crop yield, leaf area index, number of leaves, plant height, chemical analysis of leaves and fruit weight were evaluated. In the case of fruit quality, color, firmness, soluble solids content and shelf life were analyzed. It was found that the fresh weight of the harvest was higher for the chemical treatment. Regarding fruit quality, no significant differences were found between treatments.